Rethinking Incarcerated Women's Leisure as Subjected to Coercive and Normative Prison Missions - Alexis Marcoux Rouleau (Frontiers Media S.A., 2020)
Leisure is commonly understood as contributing to well-being; this is especially appealing when considering multiply marginalized populations such as incarcerated women. However, leisure is not impervious to cooptation by less benevolent social processes. In this conceptual analysis, I argue that incarcerated women's leisure must be rethought as a component of its environment and by extension, as subjected to coercive and normative prison missions. After broadly delineating incarcerated women's leisure, I determine that some characteristics of leisure can be compatible with these prison missions. I then examine individual, organizational, and social benefits and issues with leisure in women's prisons. I link these practices to reduced coerciveness and increased normativity. I conclude by suggesting that ensuring incarcerated people's well-being through leisure is not in itself an end, but a means to achieve prison's coercive and normative ends. I discuss implications for scholars, practitioners, and advocates.